War of words: Isan redshirt activists and discourses of Thai democracy. (June 2016) - Alexander, Saowanee T; McCargo, Duncan
Thai grassroots activists known as 'redshirts' (broadly aligned with former prime minister Thaksin Shinawatra) have been characterised according to their socio-economic profile, but despite pioneering works such as Buchanan (2013), Cohen (2012) and Ünaldi (2014), there is still much to learn about how ordinary redshirts voice their political stances. This article is based on a linguistic approach to discourse analysis and builds on Fairclough's (2003) arguments concerning the ways in which speakers use intertextuality and assumption to construct social and political difference and consensus. It specifically explores redshirt understandings of democracy by examining intertextuality and presupposition through various linguistic strategies. It sets out to answer these questions: What are grassroots redshirt protesters' understandings of democracy? How do they articulate those understandings verbally? The study is based on an analysis of 12 interviews conducted in 2012 with grassroots redshirts from Ubon Ratchathani, Thailand. It shows how informants voiced notions of democracy by making explicit intertextual references and alluding to implicit meaning through presupposition. The results show that informants had a definite understanding of democracy despite a degree of contradiction, confusion and ambiguity. They also attempted to communicate political beliefs despite limits on their freedom of expression.